Práctica de actividad física, deporte y niveles de sedentarismo en estudiantes universitarios - Julio Román Martínez Alvarado; Alfonso Sámano Sánchez; Ahmed Alí Asadi González; Ana Gabriela Magallanes Rodríguez; Rosalba Rosales Bonilla (Revista de Psicología y Ciencias del Comportamiento de la Unidad Académica de Ciencias Jurídicas y Sociales, 2012)
The objective of this research is to describe the practice of physical and sporting activities and levels of inactivity in mexican university students. The study included 634 university students (178 men, 456 women) between 17 and 47 years (M = 20.25, SD = 3.5) from the Centro de Ciencias de la Salud de la Universidad Autónoma de Baja California, Valle de las Palmas. Data collection was conducted within the classroom and without the presence of a professor. The results indicate that 25.4% of students play sports, while 74.6% report not do any sports. Moreover, 55% of referred students do some form of physical exercise; the other 45% of university does no exercise. The 65.3% of college students are active, meaning that regularly practice a sport or exercise; the 34.7% of the students are sedentary being most of them women, representing the 84.5%. Based on the results we can conclude that the levels of participation in sports in college are significantly lower levels of physical activity. The high percentage of sedentary is still higher in women.